Prevalence and factors associated with occupational hazard exposure among undergraduate veterinary students in Bangladesh - Pronab Das; Seemanta Das; Muhammad Abdul Mannan; Sharmin Chowdhury (Preventive Medicine Reports)
Objectives: Veterinarians are observed to be vulnerable to various occupational hazards due to the nature of their work. Veterinary students face an even greater risk, as their academic and professional training in animal handling is still incomplete. Therefore, this study aimed to investigate the prevalence of and factors associated with occupational hazard exposure among undergraduate veterinary students in Bangladesh. Methods: A cross-sectional study was conducted from August 25, 2024 to September 10, 2024 among 330 veterinary students from two conveniently selected institutions in Bangladesh. Third- to fifth-year students were invited to participate through a self-administered questionnaire. Statistical analyses were performed with the chi-square test and logistic regression to investigate the associated factors. Results: Overall, 62.4 % students reported exposure to occupational hazards. Physical hazards were the most frequently reported (44.2 %), followed by chemical (19.4 %), psychosocial (17.6 %), biological (13.6 %), and ergonomic hazards (9.1 %). Senior-level students reported a higher exposure to hazards than 3rd year students (4th year: adjusted odds ratio [AOR] = 2.45, 95 % confidence interval [CI] = 1.04, 5.74; 5th year: AOR = 2.43, 95 % CI = 1.30, 4.55). Those who received formal training outside the curriculum were more likely to report exposure (AOR = 2.49, 95 % CI = 1.16, 5.36). Moreover, a higher knowledge level was a protective factor for occupational hazards (AOR = 0.56, 95 % CI = 0.31, 0.99). Conclusion: Our findings emphasize the need for training programs both within and beyond the curriculum to improve students' practical skills, particularly among senior-level students involved in clinical duties.